Good governance and development - Singh, D.P. (2004)
In spite of the guiding principles of social justice and equity, the benefits of the India planning process have not been able to reach the marginalised groups of the pluralistic Indian society. The main reasons, among many others, is the fact that we have failed to put in place the foundations of work excellence and good work culture. Poor governance and inefficient administration in all areas of public affairs have relegated our development goals to second place. The present article, while conceptualising good governance, advocates that in order to achieve the goals of development, it is important to put our house in order first. - Reproduced.
Keywords: Good governance